2023
DOI: 10.1097/mcp.0000000000000953
|View full text |Cite
|
Sign up to set email alerts
|

Drug treatment of COVID-19 infection

Abstract: Purpose of reviewCOVID-19 pandemic has caused more than 6.6 million deaths globally. Tremendous efforts have been committed for the development of new and repurposed drugs for the treatment of COVID-19. Although different international and national guidelines share consensus in the management of COVID-19 disease with different levels of severity, new challenges have emerged, steering the need for ongoing research in advancing the clinical management of COVID-19.Recent findingsThis review focuses on recent data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…For high-risk individuals, including immunocompromised patients, certain monoclonal antibody treatments have been granted emergency use authorization. 1,2 Early administration of these treatments can potentially reduce disease progression and hospitalization rates. In severe COVID-19 cases with significant inflammatory responses, corticosteroids like dexamethasone may be used under close medical supervision.…”
Section: Cons Ider Ationsforcovid -19 Patientsinimmun Oco Mpr Omi S E...mentioning
confidence: 99%
See 2 more Smart Citations
“…For high-risk individuals, including immunocompromised patients, certain monoclonal antibody treatments have been granted emergency use authorization. 1,2 Early administration of these treatments can potentially reduce disease progression and hospitalization rates. In severe COVID-19 cases with significant inflammatory responses, corticosteroids like dexamethasone may be used under close medical supervision.…”
Section: Cons Ider Ationsforcovid -19 Patientsinimmun Oco Mpr Omi S E...mentioning
confidence: 99%
“…In the past 3 years, targets for therapeutics and strategies for prevention against coronavirus disease 2019 (COVID‐19) were identified and developed based on the pathogenesis of severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) and clinical outcomes of infection. Therapeutics for COVID‐19 regarding disease time course, symptoms and interventions, different stages of the SARS‐CoV‐2 lifecycle, and COVID‐19‐associated immunomodulatory effects were discussed by Toussi et al 1 Drug treatment of COVID‐19 infection regarding mild‐to‐moderate COVID‐19 disease in the outpatient setting, patients hospitalized with mild‐to‐moderate disease, patients hospitalized with the severe and critical disease were recently reviewed by Lui and Guaraldi 2 . Immunotherapeutics for COVID‐19 include the transfusion of high‐titer COVID‐19 convalescent plasma (CCP), treatment of anti‐SARS‐CoV‐2 monoclonal antibodies (mAbs) to COVID‐19 outpatients to prevent progression to severe disease or to people who have a high risk of severe outcomes for pre‐exposure prophylaxis purpose.…”
Section: Covid‐19 and Recent Therapeuticsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Despite some clinical trials of drugs to improve COVID-19 symptoms, there remains no consensus on effective treatment methods, and immunocompromised elderly people and children need special attention. [5][6][7][8] Previous studies have suggested that patients with COVID-19 in the acute or recovery phase exhibit changes in the microbiota, especially the gut microbiota. The alterations in these microorganisms and their metabolites may be involved in the regulation of inflammation and the immune response to mediate virus progression and symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with COVID‐19 may suffer from fever, sore throat, cough, diarrhea, sleep disorders, anxiety, depression, and cognitive impairment, which is associated with long COVID symptoms during recovery 1–4 . Despite some clinical trials of drugs to improve COVID‐19 symptoms, there remains no consensus on effective treatment methods, and immunocompromised elderly people and children need special attention 5–8 …”
Section: Introductionmentioning
confidence: 99%